A systematic review of opioid overdose interventions delivered within emergency departments. (1st August 2020) - Chen, Yanjin; Wang, Yanbin; Nielsen, Suzanne; Kuhn, Lisa; Lam, Tina
Abstract: Background: People with opioid use disorders are at higher risk of fatal opioid overdose and attend emergency departments (ED) more frequently compared to the general population. This review aimed to synthesise evidence on the ED-based delivery of opioid overdose prevention interventions. Methods: Using the PRISMA guidelines, four databases (Medline; Embase; Scopus; PsycINFO) were searched for peer-reviewed articles on ED based interventions to prevent opioid overdose, published January 1998 to October 2018. Results: The 13 identified studies were grouped into four main intervention types. Seven focused on provision of take-home naloxone (THN) and overdose education. These described the successful delivery of THN by ED staff; in collaboration with community partners; and barriers to delivery. Three studies examined medication safety interventions. These generally delivered positive outcomes on overdose-risk knowledge, but not consistently on behaviour change. One study examined buprenorphine-naloxone treatment initiation within the ED, finding positive outcomes on reported illicit drug use and treatment engagement compared to those randomised to brief intervention and referral, or referral only. Two studies explored psychosocial interventions, including motivational interviewing, which demonstrated lower non-medical prescription opioid use at follow up compared to control. Conclusions: ED provision of a range of opioid overdose prevention interventions is feasible, acceptable to patients and ED personnel. Interventions require adequate staffing/role responsibility for sustainable implementation. Most evidence was for THN, with an emerging evidence base for other intervention types reducing opioid-overdose risks in ED settings. Further research on implementation and sustainability may assist in translation of effective interventions into the ED setting.